2016
DOI: 10.1186/s12957-016-0798-4
|View full text |Cite
|
Sign up to set email alerts
|

A very rare case of a small bowel leiomyosarcoma leading to ileocaecal intussusception treated with a laparoscopic resection: a case report and a literature review

Abstract: BackgroundSmall bowel tumours are rare and comprise less than 2 % of all primary gastrointestinal neoplasms. Among these tumours, a leiomyosarcoma belonging to soft tissue sarcomas is extremely rare and accounts for about 1 % of malignant mesenchymal lesions in the gastrointestinal tract. Due to its aggressive nature and slow growth, it is often diagnosed at the late stage when curative treatment is impossible. Authors report a first case of leiomyosarcoma with chronic recurrent ileocaecal intussusception and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…It appears most commonly in the retroperitoneum, large blood vessels, and uterus, and less frequently in the lower extremities [1, 2]. Both primary and metastatic leiomyosarcoma of the small bowel are extremely rare [3]. In our case, the primary tumor is unknown since the diagnosis was made at a late stage of the disease, although clinical history strongly suggests that the lower limb might have been the origin.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It appears most commonly in the retroperitoneum, large blood vessels, and uterus, and less frequently in the lower extremities [1, 2]. Both primary and metastatic leiomyosarcoma of the small bowel are extremely rare [3]. In our case, the primary tumor is unknown since the diagnosis was made at a late stage of the disease, although clinical history strongly suggests that the lower limb might have been the origin.…”
Section: Discussionmentioning
confidence: 85%
“…However, surgery was not considered since she had disseminated disease and bowel obstruction relieved with conservative measures. In fact, intussusception often reduces spontaneously, although it can recur [3]. Small bowel metastasis by leiomyosarcoma is usually a sign of extensive disease and carries an unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Small intestinal malignant tumors are rare and comprise less than 3% of all primary GI neoplasms [ 4 ]. There are several conditions that increase the risk of development of small intestinal malignancies, including inflammatory bowel diseases such as Crohn disease, polyposis syndrome, and hereditary nonpolyposis colorectal cancer [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] Some studies have evaluated laparoscopic surgery for patients with intussusception under general conditions and have found that laparoscopic surgery is a safe and effective surgical method. [ 10 , 33 ] Laparoscopic surgery helps with accurate identification of the position and causes of the intussusception and is associated with minimal trauma and a quick recovery. In this report, 2 patients underwent laparoscopic intussusception reduction and ileal tumor resection.…”
Section: Discussionmentioning
confidence: 99%